South Africa's foreign policy of quiet diplomacy towards Zimbabwe : constructivism as a framework to highlight the contradictory norms of human rights and African solidarity - Coetzee, Cari (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2004.